Continuous intravenous anakinra for treating severe secondary haemophagocytic lymphohistiocytosis/macrophage activation syndrome in critically ill children. Issue 9 (11th June 2021) - Charlesworth, James E.G.; Wilson, Shaun; Qureshi, Amrana; Blanco, Esther; Mitchell, Amy; Segal, Shelley; Kelly, Dominic; Weitz, James; O'Shea, Deirdre; Bailey, Kathryn; Kavirayani, Akhila
Abstract: The cytokine storm of secondary haemophagocytic lymphohistiocytosis (sHLH)/macrophage activation syndrome (MAS) can cause life‐threatening multiorgan failure. Interleukin‐1 (IL‐1) receptor blockade with anakinra can be effective in the management of sHLH/MAS. Subcutaneous (SC) dosing regimens are widely described; however, intravenous (IV) dosing is advantageous where time‐critical intervention is vital and where SC oedema and/or hypoperfusion limits absorption. We review three critically ill children (aged 9, 11 and 17) with sHLH and rapidly progressive multiorgan dysfunction, successfully treated with continuous IV anakinra infusion. This case series significantly enhances the incipient knowledge regarding the safety and efficacy of IV anakinra for life‐threatening sHLH.